(untitled) (Research, Society and Development, 2024)
Diagnosing Autism Spectrum Disorder requires extensive investigation to get treatment right from the start. Given this, Applied Behavior Analysis - ABA aims to evaluate the delayed or absent skill, going through each step to achieve effective form. One of the objectives of ABA is to validate the skills that a person with autism has mastered and teach the skills that they have not yet mastered. The general objective of this study was to understand the benefits of ABA for the treatment of adults with Autism Spectrum Disorder - ASD. The preparation of the present study with regard to the procedure used a narrative, exploratory and explanatory bibliographical research. Materials from 2000 to 2023 were used as published base work to provide important contributions to the proposed topic, and the keywords: ASD, ABA, ABA . Adult Patients. Therefore, we analyze that the application of ABA in adults requires a personalized and respectful approach that takes into account the individual preferences, needs and goals of the autistic adult. The results of this study suggest that this patient’s social integration can be achieved through the development of autonomy and greater independence in daily activities, expanding functional skills and better quality of life for everyone involved in their social situation.